Students’ Perception on Using English Swara YouTube as a Learning Media of Speaking Skill at the 12th Grade at SMAN 1 Cikande - Galuh Novalia; Siti Suharsih; Eri Rahmawati (Journal of Linguistics, Literacy, and Pedagogy, 2023)
This research aims to find out how SMAN 1 Cikandestudents perception about using English Swara YouTube as a learning media of speaking skill, as well as to find out the benefits that students get. Qualitative descriptive was used in this research. The instrument applied during the study were used questionnaires and interviews. The population of this research were XII IPA 2 Class of SMAN 1 Cikande with 36 participants. The finding of this research demonstrated that students had a favorable opinion of using English Swara YouTube as a learning medium of speaking skill. The respondents positively responded to using English Swara YouTube based on their own learning experience. English Swara YouTube had good impact in practicing speaking after students watched the material from English Swara YouTube. using English Swara YouTube as a learning media for speaking skill, they found it interesting and effective. This study also shows the benefit that they get from using English Swara YouTube as a learning media of speaking skill, it can increase the number of new words and minimizes students' fears to pronounce words. A suggestion for future research is to explore more about students' perception of using English Swara YouTube as a learning media in all English skill such as listening, writing, not only speaking, and explore further the obstacles that students face. KeywordsPerception, English Swara YouTube, Speaking Skill